Photoactivated carbon dots immobilized on cellulose for antibacterial activity and biofilm inhibition - Sreeshna Ravindran; Remya Radha; Tala Terro; Rasha Diab; Abdelhamid Khodja; Mohammad H. Al-Sayah (Scientific Reports)
Abstract Pathogenic bacterial infections represent a major threat to human health, which is worsened by the rise of antibiotic resistance stemming from misuse. Carbon dots (CCM-PBA-NH2) were synthesized and examined for their potential as photo-activated antimicrobial agents to address this issue. Various characterization methods were employed to investigate the structure and morphology of the CCM-PBA-NH2 carbon dots (CDs). Techniques including UV-VIS and fluorescence spectroscopy, FTIR, zeta potential analysis, Raman spectroscopy, XRD, SEM and TEM were utilized to assess their physicochemical properties, such as size, shape, surface functionalities and charge distribution. These carbon dots exhibited strong antibacterial activity against both Gram-positive and Gram-negative bacteria. They effectively prevented biofilm formation and disrupted preformed biofilms while displaying low cytotoxicity toward mammalian cells at concentrations of 0.1 mg/mL. The antibacterial properties of carbon dots were also evaluated on cellulose and oxidized cellulose fiber surfaces, where a significant reduction in bacterial growth was noted. CD-modified oxidized cellulose displayed strong adhesion, positioning carbon dots as a promising candidate for use in antimicrobial materials, including wound dressings and sterilization tools. Combining carbon dots with biocompatible carriers, like cellulose, presents a versatile and effective strategy for fighting bacterial infections.